2021
DOI: 10.1101/2021.07.03.451026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunisation of ferrets and mice with recombinant SARS-CoV-2 spike protein formulated with Advax-SM adjuvant protects against COVID-19 infection

Abstract: The development of a safe and effective vaccine is a key requirement to overcoming the COVID-19 pandemic. Recombinant proteins represent the most reliable and safe vaccine approach but generally require a suitable adjuvant for robust and durable immunity. We used the SARS-CoV-2 genomic sequence and in silico structural modelling to design a recombinant spike protein vaccine (Covax-19). A synthetic gene encoding the spike extracellular domain (ECD) was inserted into a baculovirus backbone to express the protein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…It is interesting that in our study the 2.5 µg dose induced higher levels of antibodies than the 5 µg dose. Indeed, similar observations of inverse spike protein dose effects on antibody production was seen in a previous ferret study using the same spike protein as used here 11 and was also reported in the Novavax Phase I study where the lower 5 μg dose in the study was associated with higher antibody levels than the much higher 25 μg dose 18 . This suggests that excess doses of spike protein may in some way modulate and suppress the humoral immune response, thereby explaining why lower doses could result in high antibody responses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is interesting that in our study the 2.5 µg dose induced higher levels of antibodies than the 5 µg dose. Indeed, similar observations of inverse spike protein dose effects on antibody production was seen in a previous ferret study using the same spike protein as used here 11 and was also reported in the Novavax Phase I study where the lower 5 μg dose in the study was associated with higher antibody levels than the much higher 25 μg dose 18 . This suggests that excess doses of spike protein may in some way modulate and suppress the humoral immune response, thereby explaining why lower doses could result in high antibody responses.…”
Section: Discussionsupporting
confidence: 87%
“…The spike ECD has an amino acid sequence corresponding to wild-type SARS-CoV-2 (Wuhan strain) together with some stabilizing mutations. This spike ECD protein has been previously characterized in mice and ferrets as part of a vaccine called COVAX-19/SpikoGen 11 that has progressed through phase III clinical trials and recently received emergency use authorization in Iran 5 . Adjuvants are generally needed to increase the effectiveness of subunit vaccines 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Advax can be used in combination with a CpG oligonucleotide (Advax-CpG) that stimulates TLR-9, which results in even stronger activation of humoral and cellular immunity (41). Advax-CpG adjuvant efficacy has been demonstrated to be effective in vaccines against tuberculosis (41,42), Alzheimer's disease (43), and coronavirus disease 2019 (COVID)-19 (44), among others. This study also tested the SWE squalene emulsion adjuvant that mimics the wellknown MF59 adjuvant (Sequirus, USA) included in commercial influenza vaccines (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…The vaccines are based on wild-type SARS-CoV-2 (Wuhan strain) spike protein ECD with a histidine tag to assist with purification and stabilization that is expressed in insect cells using the baculovirus transfection system. This spike protein ECD antigen when combined with Vaxine's proprietary Advax-CpG55.2 has previously been shown to be immunogenic, protective, and safe in mice and ferrets in an Australian-developed vaccine called COVAX-19 or SpikoGen ( 28 ) that has already successfully passed phase III clinical trials and in October 2021 received emergency use authorization for human adult use from the Iranian FDA ( 23 ). This same spike protein ECD when formulated with a squalene O/W (SWE) adjuvant (NARUVAX-C19 vaccine) provided complete protection of Syrian hamsters against SARS-CoV-2 infection and prevented transmission to naïve animals placed in the same cage as the challenged animals ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed methodology of obtaining recombinant spike protein ECD has been described previously ( 23 ). Briefly, the spike protein was identified from the SARS-CoV-2 genomic sequence in NCBI (access number: NC 045512) ( 24 ).…”
Section: Methodsmentioning
confidence: 99%